Measurement sensitivity characteristics investigation of an optical fiber sagnac interferometer through strain sensing - Teo, Hwee Fang (2014)
This report encloses the author’s attempts in the investigation of the measurement sensitivity characteristics of an Optical Fiber Sagnac Interferometer (OFSI) through strain sensing. As many literatures have shown that OFSIs are extensively investigated for various sensing applications, efforts were put in to theoretically analyze and experimentally verify certain parameters. The parameters used are to realize how the optical phase difference of the Sagnac loop would affect the measurement sensitivity characteristics of the OFSI as defined through the birefringence and length of the optical fiber, along with the fringe order of the interference transmission spectra.